The Transpalpebral Versus the Transciliary Variant of the Supraorbital Keyhole Approach: Anatomic Concepts for Aneurysm Surgery. Issue 1 (12th December 2019) - Rychen, Jonathan; Zumofen, Daniel W; Riina, Howard A; Mariani, Luigi; Guzman, Raphael
Abstract: BACKGROUND: The supraorbital craniotomy (SOC) is classically performed through a skin incision in the patient's eyebrow. A variant with a skin incision in the patient's eyelid has become increasingly popular in recent years. OBJECTIVE: To compare the transpalpebral and the transciliary variants of the SOC with regard to their potential role in aneurysm surgery. METHODS: We carried out cadaveric dissections and virtual craniotomies on computerized tomography datasets. The skin incision, the craniotomy location and size, the working angles, and the achievable exposure of neurovascular structures were assessed and compared for both variants of the SOC. RESULTS: The skin incision measured 4 cm for the transpalpebral and 3 cm for the transciliary variant. The skin could be retracted 1.5 cm upward from the lower edge of the orbital rim with the transpalpebral and 2.5 cm upward with the transciliary variant. The craniotomy size was 2.5 × 1.5 cm for both variants, given that the transpalpebral variant included an orbital osteotomy. The bony opening in the transpalpebral variant was 1 cm more caudal; this restricted the craniocaudal working angles and, thereby, limited the achievable exposure of neurovascular structures in the paraclinoid area and along the sphenoid ridge. CONCLUSION: If the orbital rim and the anterior aspect of the orbital roof are removed, then the transpalpebral variant of the SOC enables a bony opening that is just as large as that of the transciliary variant. Nonetheless, the more caudal location of the bony opening alters the available working angles and may impede exposure of key structures during aneurysm surgery.